Stabilization of Continuous-Time Fractional Positive Systems by Using a Lyapunov Function - Benzaouia, Abdellah; Hmamed, Abdelaziz; Mesquine, Fouad; Benhayoun, Mohamed; Tadeo, Fernando (IEEE transactions on automatic control, 2014)
The stabilization problem for continuous-time fractional linear systems with the additional condition of non negativity of the states is solved. The obtained results are based on a direct Lyapunov function. In particular, the synthesis of state-feedback controllers is obtained by giving conditions in terms of Linear Programs. The solution is also extended to stabilization by asymmetric bounded control. Illustrative examples are provided to show the usefulness of the results.